EVALUASI IMPLEMENTASI KEBIJAKAN PENGELOLAAN KELESTARIAN KAWASAN DANAU MANINJAU DI KABUPATEN AGAM - Cindera Billova; Adil Mubarak (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
The purpose of this research is to evaluate or assess the implementation of policy whether the policy has been running optimally and whether the policy is feasible to proceed. This research is qualitative research with descriptive method. The selection of speakers is done by purposive sampling. Data collection is done by interview and documentation studies, to analyze the data is done by presenting data, data reduction, and data verification. The instrument used in this study was the researcher himself, for guiding interviews using several questions that had been prepared, while to support documentation related to the research, the data collection tool used was Mobile, which serves to record which makes it easy to compile data and the validity of the data is done by source triangulation method. So, it can be concluded that the results of this study are that the policy for the management of Lake Maninjau sustainability has not been running optimally and the objectives of the policy have not yet been reached.